Perancangan Logo dan Media Promosi Pulau Mengare Gresik Berbasis Edukasi Sebagai Upaya Mengenalkan Wisata Sejarah - Putri, Dinda Cholifah; Bahruddin, Muhammad; Khoiriqqoh, Abdullah (Jurnal Art Nouveau, 2016)
The purpose of designing this Mengare Island media campaign is to introduce and preserve the historical heritage Mengare . The study was conducted using qualitative research is to conduct interviews , observation , documentation , and literature to obtain data to support the drafting . Data were analyzed using multiple stages of data reduction , data presentation and conclusion. From these results we found the concept of